The effect of a session of moderate intensity aerobic exercise on inflammatory factors and flow-mediated dilation in pre-menopausal and post-menopausal women - Arsalan Damirchi; Sanaz Shiravi (Shahid Beheshti University, 2024)
Background and purpose: Cardiovascular diseases are the most important cause of death among women. Hormonal changes around and after menopause can affect inflammatory factors such as interleukins and tumor necrosis factor alpha (TNF-α) as well as vascular function. The aim of this research was to determine the effect of a session of aerobic exercise with moderate intensity on interleukins 6 and 8, TNF-α, as well as vascular function (flow mediated dilation) in premenopausal and postmenopausal women.Materials and methods: In this semi-experimental study, 30 inactive women without any cardiovascular disease participated in the study voluntarily, which were allocated into two equal groups (n=15) of premenopausal women (age, 47.7±1.3 years) and postmenopausal women (age, 56.8±1.5 years). Participants in both groups performed a session of moderate intensity aerobic exercise included 30 min of running on a treadmill at 60-70% of heart rate reserve. Participants' blood samples were collected 30 min before and 30 min after the exercise and were analyzed to measure inflammatory factors (interleukin 6, interleukin 8 and TNF-α). Vascular function was evaluated by measuring flow mediated dilation at 15 min before and 15 min after aerobic exercise. Data were analyzed by using SPSS software and covariance test (P>0.05).Results: In response to a session of moderate intensity aerobic exercise, no significant difference was seen in interleukin 6 and 8 between two groups of premenopausal and postmenopausal women (P=0.432, P=0.097), but TNF-α decreased significantly in premenopausal whereas it it did not change in postmenopausal women (P=0.003). In addition, vascular dilation after a session of moderate intensity aerobic exercise was significantly (P=0.001) different between premenopausal and postmenopausal women , where, flow mediated dilation increased in premenopausal compared to postmenopausal women.Conclusion: Based on the increased FMD and decreased TNF-α in premenopausal women, in general our findings show that following acute exercise factors associated with endothelial responsiveness are improved in premenopausal women while responses are decreased in postmenopausal womenHowever, lack of differences in interleukins 6 and 8 between premenopausal and postmenopausal women might indicate increased inflammation in premenopausal women, which is a reason for the onset or increases in disorders of endothelial function during menopause.